PENGARUH PENGAWASAN DAN PEMBERIAN MOTIVASI TERHADAP KINERJA KARYAWAN DI HOTEL MONA PLAZA PEKANBARU - Sianipar, Paris; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of monitoring and providing motivation on employee performance at Hotel Mona Plaza. Supervision and motivation as the independent variable (X) and employee performance as the dependent variable (Y), and this study takes the number of respondents was 53 respondents.Data obtained through questionnaires selanjtnya processed to then be tested through descriptive analysis and statistical analysis such as multiple linear regression analysis, t test, and correlation analysis and determination with the help of using SPSS.The results showed that the results of hypothesis testing t test, t (2.892)> t table (2.009) and t (2.807)> t table (2.009). This means that the supervision and motivation have a significant effect on employee performance. The magnitude of the effect of monitoring and providing motivation to employees performance at the Mona Plaza Hotel Pekanbaru is 24.3% and the remainder were not included in this research model.Keywords: Monitoring, Giving Motivation, Performance, Mona Plaza Hotel